Role of Technology Readiness in Airline Passengers’ Perceptions ofSelf-service Technology Quality - Ekkarat Suwannakul (African Journal of Hospitality Tourism and Leisure, 2021)
Self-service technology (SST) is more crucial now than before for the service delivery of airlines. Many airlines employ various types of SSTs so that passengers can perform certain services on their own. Although many passengers enjoy using the self-service option, some are not ready to adopt such a technology. This study aims to investigate how passengers possessing different characteristics perceive technology readiness (TR) and examine the influence of TR on perceived SST quality. Questionnaires were used to collect data from airports in Bangkok, Thailand. A total of 382 usable data were analysed using one-way ANOVA and multiple regression analysis. Results indicate significant differences in TR across age, education, occupation, income, types of SSTs and air travel frequency. This study also reveals that TR dimensions, namely, optimism, innovativeness, anxiety and insecurity, are important factors influencing airline passengers’ perceptions of SST quality.
Keywords: Technology Adoption and User Behaviour; Digital Marketing and Social Media; Impact of AI and Big Data on Business and Society